(untitled) (Research, Society and Development, 2020)
Throughout the gestational period, the female body undergoes numerous transformations for the preparation of fetal growth, labor and changes in the puerperium, during the period between the expulsion of the placenta and the return to the pre-gravid condition, being divided in the immediate postpartum, late postpartum and postpartum remote, is a period that as the psychic, physical and motor transformations become evident, mainly to musculoskeletal alterations. The physiotherapist is one of the professionals who perform a longer work in the woman’s life, working with the pilates method, which brings a rehabilitation proposal and dynamic capacity, adding a practice of physical activity to mental relaxation, concentration exercise, correction of The movement and fluidity, improving the posture, always attending as physiological curvatures of the body minimizing as compensations of that period. To identify pilates methodologies in postpartum women, and as the main musculoskeletal changes. An electronic version of the Scielo, Lilacs and Medline database was performed between 2008 and 2017. Initially, the research was subdivided into two categories, the first one was searched as "major musculoskeletal changes in puerperal women", following a search on "the pilates method in the puerperium" for a better analysis and search of the data. In the end, there were 132 articles with 2 categories, where a total of 35 articles were excluded, as it does not fit the inclusion criteria. Allowing for a consistency and a generalization in the results of the CHANGES working groups, as well as the importance of physiotherapy with pilates in a puerperal process. That there are many musculoskeletal muscles in the puerperium, and that an physiotherapist and their physiological massage is the endurance of the body of human handicap, flex.